Loss of cardiac myosin light chain kinase contributes to contractile dysfunction in right ventricular pressure overload. Issue 7 (5th April 2022) - Prasad, Vidhya; Makkaoui, Nour; Rajan, Rohan; Patel, Alisha; Mainali, Bipul; Bagchi, Pritha; Kumar, Rhea; Rogers, Julia; Diamond, Jake; Maxwell, Joshua T.
Abstract: Nearly 1 in every 100 children born have a congenital heart defect. Many of these defects primarily affect the right heart causing pressure overload of the right ventricle (RV). The RV maintains function by adapting to the increased pressure; however, many of these adaptations eventually lead to RV hypertrophy and failure. In this study, we aim to identify the cellular and molecular mechanisms of these adaptions. We utilized a surgical animal model of pulmonary artery banding (PAB) in juvenile rats that has been shown to accurately recapitulate the physiology of right ventricular pressure overload in young hearts. Using this model, we examined changes in cardiac myocyte protein expression as a result of pressure overload with mass spectrometry 4 weeks post‐banding. We found pressure overload of the RV induced significant downregulation of cardiac myosin light chain kinase (cMLCK). Single myocyte calcium and contractility recordings showed impaired contraction and relaxation in PAB RV myocytes, consistent with the loss of cMLCK. In the PAB myocytes, calcium transients were of smaller amplitude and decayed at a slower rate compared to controls. We also identified miR‐200c, which has been shown to regulate cMLCK expression, as upregulated in the RV in response to pressure overload. These results indicate the loss of cMLCK is a critical maladaptation of the RV to pressure overload and represents a novel target for therapeutic approaches to treat RV hypertrophy and failure associated with congenital heart defects. Abstract : Many congenital heart defects primarily affect the right heart causing pressure overload of the right ventricle (RV) and eventually lead to RV hypertrophy and failure. We found pressure overload of the RV induced significant downregulation of cardiac myosin light chain kinase (cMLCK), which lead to impaired contraction and relaxation in PAB RV myocytes consistent with cMLCK loss, and also found upregulation of miR‐200c, which has been shown to regulate cMLCK expression. These results indicate the loss of cMLCK is a critical maladaptation of the RV to pressure overload and represents a novel target for therapeutic approaches to treat RV hypertrophy and failure associated with congenital heart defects.